Structural racism and its psychological and social consequences in Richard Wright’s Native Son - Eka Nurcahyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study examines the representation of structural racism and its psychological and social consequences in Richard Wright’s Native Son (1940) through the lens of African American literary criticism. An interdisciplinary framework integrating historical, socio-cultural, political, economic, and psychological perspectives situates the novel within the context of the Great Depression and the Great Migration. Instead of treating racism as a background condition, this study conceptualizes it as a structural system that operates through institutions such as housing, education, employment, and the legal system while simultaneously shaping individual consciousness and social behavior. The analysis demonstrates how racial segregation, economic deprivation, and social exclusion constrain individual agency and contribute to feelings of inferiority, hopelessness, alienation, and criminalized resistance, as embodied by the protagonist, Bigger Thomas. The study argues that Wright’s novel exposes racism as a structural force that deforms both personal identity and social relations, challenging dominant narratives of individual responsibility and moral failure.